Estimation of saturated hydraulic conductivity using emitter discharge rate and saturated radius - M. S. M .Amin (Malaysian Society of Soil Science, 2023)
The saturated hydraulic conductivity of soil is needed for determining the agricultural and hydrological processes. The measurement techniques used to estimate such property remain hampered by extensive labor and time constraints. In this study both emitter discharge rate and steady saturated radius on the soil surface were used to determine the saturated hydraulic conductivity using Wooding’s equation. Field experiments on sandy and sandy loam soils were conducted to estimate the saturated hydraulic conductivity based on point source trickle irrigation. The results showed that predicted saturated hydraulic conductivity values were within 23% and 26% of measured values as estimated under laboratory condition.